The Effect of Fear of Coronavirus (Covid-19) on Attitudes Toward Cancer Screening - Sayilan, Samet; Aydin Sayilan, Aylin; Ozen, Nurten (Asian Pacific Journal of Cancer Biology, 2022)
Background: Although cancer screening plays a critical role in the early detection of cancer, fear caused by the Covid-19 pandemic is reported to have significantly obstructed cancer screening programs. The purpose of this study was to determine the effect of fear of coronavirus (Covid-19) on attitudes toward cancer screening. This descriptive, cross-sectional study was completed with 300 individuals. The data were collected from patients presenting to the clinic of an education and research hospital between April and July, 2021. An information form, the Fear of Covid-19 Scale, and the Attitude Scale for Cancer Screening were employed as data collection tools. Results: The mean age of the participants was 46.66±13.39 years, 56.7% were women, and 44% were university graduates. The mean Fear of Covid-19 Scale score was 20.53, and the mean Attitude Scale for Cancer Screening score was 99.79. Conclusion: Participants in this study experienced a moderate level of fear and exhibited positive attitudes toward cancer screening programs, although positive attitudes regarding cancer screening decreased as fear of Covid-19 increased.